PENGEMBANGAN APLIKASI PEMBELAJARAN MATEMATIKA MATERI BARISAN DAN DERET BERBASIS ANDROID MELALUI ISPRING SUITE 11 - Abrar, Andi Ika Prasasti; Masnaeni, Masnaeni; Rahmi, Rahmi; Faradila, Rista; Hidayat, Muh. Nur (Jurnal Dedikasi Pendidikan, 2025)
In the digital era, technology plays an important role in supporting educational transformation, particularly in creating flexible learning that suits the characteristics of students. The Merdeka Curriculum supports the use of technology in learning activities, including the development of Android-based learning media. The uniqueness of this application lies in the direct integration between PowerPoint, iSpring Suite 11, and conversion to the Android platform, which allows media creation without coding. This study aims to create a mathematics learning application focused on the topic of sequences and series using iSpring Suite 11. This research is a development study that applies the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 26 tenth-grade students at MAS Madani Alauddin. Data were obtained through expert validation, questionnaires involving teachers and students, as well as tests measuring learning outcomes. The findings of the study indicate that the developed learning media falls into the very valid category, with a score of 91% from material experts and 92% from media experts. The average score achieved by the students reached 87, which is categorized as very high. Therefore, the mathematics learning application developed using iSpring Suite 11 for the Android platform is considered valid, practical, and efficient as an interactive learning media option that supports the mathematics learning process in the digital era